Consumer perceptions of Prime bevarages' marketing tools - Lazareva, Varvara (2024)
The purpose of this thesis is to explore the innovative marketing tactics used by Prime Beverages to stand out in the market and the consumers’ perception of them. It explores the effectiveness of these tactics, in particular by paying close attention to the role of digital marketing and social media on the brand’s success. The research is done through a theoretical analysis and an empirical study involving an online survey among respondents. The findings highlight how strategic social media promotion and influencer endorsements increase consumer engagement and trust, and therefore enhance brand visibility and its’ position in the beverage market. The study suggests that adapting to digital trends and consumer expectations is crucial for brand success.